2019
DOI: 10.1101/749861
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel Quorum Sensing Activity in East Antarctic Soil Bacteria

Abstract: Antarctica, being the coldest, driest and windiest continent on Earth, represents the most extreme environment a living organism can thrive in. Under constant exposure to harsh environmental threats, terrestrial Antarctica remains home to a great diversity of microorganisms, indicating that the soil bacteria must have adapted a range of survival strategies that require cell-to-cell communication. Survival strategies include secondary metabolite production, biofilm formation, bioluminescence, symbiosis, conjuga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…Antarctica is the coldest, driest, and windiest continent and is considered one of the harshest environments for biodiversity (Chown et al, 2015;Wong et al, 2019), yet it harbors surprisingly complex communities with high bacterial diversity (Smith et al, 2010). The diversity and composition of soil microbiomes in Antarctica have been documented in several studies (O'Brien et al, 2004;Wong et al, 2011;Bottos et al, 2014;Peixoto et al, 2016;Malard and Pearce, 2018;Malcheva et al, 2020;Zhang et al, 2020) which have shown that bacterial communities across Antarctic soils vary significantly not only with climate, geography and local biological influences, but also with plant type (Griffiths et al, 2011;Xiong et al, 2012;Yun et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Antarctica is the coldest, driest, and windiest continent and is considered one of the harshest environments for biodiversity (Chown et al, 2015;Wong et al, 2019), yet it harbors surprisingly complex communities with high bacterial diversity (Smith et al, 2010). The diversity and composition of soil microbiomes in Antarctica have been documented in several studies (O'Brien et al, 2004;Wong et al, 2011;Bottos et al, 2014;Peixoto et al, 2016;Malard and Pearce, 2018;Malcheva et al, 2020;Zhang et al, 2020) which have shown that bacterial communities across Antarctic soils vary significantly not only with climate, geography and local biological influences, but also with plant type (Griffiths et al, 2011;Xiong et al, 2012;Yun et al, 2014).…”
Section: Introductionmentioning
confidence: 99%